Genetic variation in photosynthetic performance and tolerance to osmotic stress (desiccation, freezing, hyposalinity) in the rocky littoral foundation species Fucus vesiculosus (Fucales, Phaeophyceae). Issue 5 (15th September 2016) - Rothäusler, Eva; Sjöroos, Joakim; Heye, Katharina; Jormalainen, Veijo
Abstract : Genetic diversity may play an analogous role to species diversity, as it can contribute to ecosystem function and stability, and provision of ecosystem services. In the Baltic Sea, perennial algal beds are often comprised of only Fucus vesiculosus and the amount of genetic variation in fitness‐related traits (i.e., the ability of the alga to photosynthesize or withstand stress) will thus determine the alga's local persistence in a changing environment. To study genetic variation in the crucial traits behind persistence we grew replicate vegetative branches that came from the same genotype in common gardens. We quantified osmotic stress tolerance and recovery responses by exposing branches to desiccation, freezing, and hyposalinity regimens. Our results show that genetic variation among genotypes was apparent for some photosynthetic parameters (maximal electron transport rate, saturation irradiance for electron transport, nonphotochemical quenching) and growth. Algae tolerated freezing (1, 440 min at −2.5°C) and hyposalinity (1, 560 min at 2.5) well, but did not recover from desiccation (70 min at 12°C, causing ~94% water loss). Furthermore, we found very little if any evidence on genetic variation in tolerance to these stressors. Our results suggest that low salinity and cold winters in the northern marginal populations selected for hyposalinity and freezing tolerant genotypes, possibly eroding genetic variation in tolerance, but that tolerance to harsh desiccation has been lost, likely due to relaxed selection. The overall availability of genetic variation in fitness related traits might be supportive for F. vesiculosus during adaptation to gradual changes of its environment.